PW 1917 Building the evidence base for river drowning prevention: the australian experience. (November 2018) - Peden, Amy E; Franklin, Richard C; Leggat, Peter A
Abstract : Background: Rivers are a leading location for drowning internationally. To understand how to prevent river drowning, multiple perspectives are required. We present the results of a multi-phase study. Objective: To understand and prevent river drowning. Methods: Methods used included a systematic literature review, epidemiological analysis of coronial data, surveillance program (community survey and breathalysing), representative CATI survey of adults and a Delphi process prioritising prevention strategies. Findings: The literature review identified limited information globally. Epidemiological studies confirmed: rivers as the leading drowning location in Australia (27%); males, alcohol, flooding and remoteness as risk factors; and only 8% of river drowning cases had coronial recommendations. While males account for 80% of river drowning statistics, the CATI survey identified similar numbers of males and females visit rivers, albeit for different activities. Older people, once adjusted for exposure, had the greatest relative risk of river drowning. Findings of the surveillance program (including community surveys and breathalysing) show rivers are a fluid environment with a diversity of activities being undertaken by people of different ages. Alcohol usage was more prevalent in the afternoon and early evenings, with both males and females recording positive readings for alcohol; with 7% recording a blood alcohol content ≥0.05%. River visitation patterns are influenced by time of day, weather and day of week. Conclusions: Rivers are a constantly changing and complicated environment, used by a diverse range of people for a wide variety of activities. The prevention of river drowning represents a wicked problem, where usage of such locations is encouraged and often unregulated. Currently there is limited evidence available for the prevention of river drowning. Further research is required (both in Australia and internationally). Policy implications: Both males and females should be targeted through public awareness and education campaigns, including those around alcohol-related drowning risk. Acknowledgement: This research is supported by Royal Life Saving Society – Australia. The drowning prevention research of Royal Life Saving Society – Australia is supported by the Australian Government.